A Systematic Review: Is Aedes albopictus an Efficient Bridge Vector for Zoonotic Arboviruses? - Taissa Pereira-dos-Santos; David Roiz; Ricardo Lourenço-de-Oliveira; Christophe Paupy (Pathogens, 2020)
Mosquito-borne arboviruses are increasing due to human disturbances of natural ecosystems and globalization of trade and travel. These anthropic changes may affect mosquito communities by modulating ecological traits that influence the “spill-over” dynamics of zoonotic pathogens, especially at the interface between natural and human environments. Particularly, the global invasion of Aedes albopictus is observed not only across urban and peri-urban settings, but also in newly invaded areas in natural settings. This could foster the interaction of Ae. albopictus with wildlife, including local reservoirs of enzootic arboviruses, with implications for the potential zoonotic transfer of pathogens. To evaluate the potential of Ae. albopictus as a bridge vector of arboviruses between wildlife and humans, we performed a bibliographic search and analysis focusing on three components: (1) The capacity of Ae. albopictus to exploit natural larval breeding sites, (2) the blood-feeding behaviour of Ae. albopictus, and (3) Ae. albopictus’ vector competence for arboviruses. Our analysis confirms the potential of Ae. albopictus as a bridge vector based on its colonization of natural breeding sites in newly invaded areas, its opportunistic feeding behaviour together with the preference for human blood, and the competence to transmit 14 arboviruses.